2022
DOI: 10.1021/acs.energyfuels.2c01723
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Clathrate Hydrate Science

Abstract: Clathrate hydrates are extremely important in the area of energy and fuels as both potential hydrocarbon resources and nuisances or hazards in the oil and gas industry. They are ubiquitous in nature, occurring in many places on Earth and probably many more extraterrestrial bodies. They have potential for the storage and transport of hydrocarbons, as a storage medium for hydrogen for fuel cells, and for cold energy storage. Other possible applications include CO 2 sequestration, desalination, gas separations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 227 publications
0
14
0
Order By: Relevance
“…Ratcliffe presented a review on the development of the clathrate hydrate science over its roughly 200 year history. 27 Zhu et al 28 reported an account of the use of Raman spectroscopy to identify the structure and molar composition of hydrate and how in situ information on the kinetics of formation, decomposition, replacement, and molecular diffusion at the molecular level is obtained. Pan et al 29 analyzed natural gas hydrate samples spatially resolved using Raman spectroscopy to identify whether these natural samples only show heterogeneity with regard to their cage occupancy and composition or whether they already show coexistent phases.…”
Section: ■ Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratcliffe presented a review on the development of the clathrate hydrate science over its roughly 200 year history. 27 Zhu et al 28 reported an account of the use of Raman spectroscopy to identify the structure and molar composition of hydrate and how in situ information on the kinetics of formation, decomposition, replacement, and molecular diffusion at the molecular level is obtained. Pan et al 29 analyzed natural gas hydrate samples spatially resolved using Raman spectroscopy to identify whether these natural samples only show heterogeneity with regard to their cage occupancy and composition or whether they already show coexistent phases.…”
Section: ■ Fundamentalsmentioning
confidence: 99%
“…Ratcliffe presented a review on the development of the clathrate hydrate science over its roughly 200 year history . Zhu et al reported an account of the use of Raman spectroscopy to identify the structure and molar composition of hydrate and how in situ information on the kinetics of formation, decomposition, replacement, and molecular diffusion at the molecular level is obtained.…”
Section: Fundamentalsmentioning
confidence: 99%
“…Gas hydrates are crystalline compounds that form when guest molecules (such as methane, ethane, and propane) are trapped in cages formed by water molecules. , The Lingshui gas field in the South China Sea is approaching production with a water depth of 1252.2–1530.5 m. The high-pressure and low-temperature environment of the deep water is prone to hydrate formation, causing pipeline blockages. Once blockage occurs, the production will be jeopardized, causing huge economic losses and may even lead to serious accidents and casualties. Therefore, hydrate blockage prevention is of great significance in the development of the Lingshui gas field. …”
Section: Introductionmentioning
confidence: 99%
“…Clathrate hydrates are crystalline water‐based inclusion compounds with gas molecules trapped in the cavities formed by the ice–water networks. They have been extensively studied due to their technological applications 1–35 . For example, the CO 2 clathrate hydrates are of interest driven by their potential use in CO 2 gas capture and storage from the Earth's atmosphere, and control climate change, 36–38 while in an astrophysical context their formation and presence could influence the composition and stability of planetary ices and comets 39–41 .…”
Section: Introductionmentioning
confidence: 99%